1995
DOI: 10.3109/10520299509108312
|View full text |Cite
|
Sign up to set email alerts
|

A Quick Embedding Method for Light Microscopy and Image Analysis of Cotton Fibers

Abstract: A quick embedding method using UV polymerization of methacrylate plastic has been devised for embedding fibers encased in a polyvinyl chloride tube. The resulting embedments are suitable for light microscopy and image analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 2 publications
0
24
0
Order By: Relevance
“…Cross-sectioning is the most significant step in obtaining analysable images of fibres. A bundle of fibres embedded in a polymer resin is cut (Annis & al., 1992;Boylston & al., 1995) and the surface containing the fibre cross sections is imaged on a microscope by reflected light (Annis & al., 1992). Image segmentation is a computational process that separates cotton cross sections from the image background from one another.…”
Section: Indirect Methodsmentioning
confidence: 99%
“…Cross-sectioning is the most significant step in obtaining analysable images of fibres. A bundle of fibres embedded in a polymer resin is cut (Annis & al., 1992;Boylston & al., 1995) and the surface containing the fibre cross sections is imaged on a microscope by reflected light (Annis & al., 1992). Image segmentation is a computational process that separates cotton cross sections from the image background from one another.…”
Section: Indirect Methodsmentioning
confidence: 99%
“…In preparation for cutting fiber cross-sections, the CSIRO followed the detailed technique reported by Boylston et al 26,27 and used routinely at the USDA to prepare fiber bundles and resin embed the bundle. Given that the aim of the procedure is to obtain quantitative fiber cross-sectional dimensions by viewing the prepared thin fiber cross-sections under the optical microscope, Boylston et al focused on two critical issues in the development of this procedure.…”
Section: Preparation Of Fiber Cross-sections and Optical Microscopymentioning
confidence: 99%
“…It is noted that Hequet et al 25 recently reported a further refinement of this process by mounting the fiber bundle in thinner 1/16-inch internal diameter tubing to further reduce the likelihood of errors due to the fiber axis not being at right angles to the cutting plane during the sectioning process. Note that for all the results reported in this paper the fibers were mounted at the CSIRO following Boylston et al's 26,27 original procedure, that is, the fiber bundle was mounted in 1/8-inch internal diameter tubing. This study does not address the likely errors/benefits from adopting the two different tubing sizes for mounting the fiber bundle.…”
Section: Preparation Of Fiber Cross-sections and Optical Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Fiber identification methods using image-processing techniques generally take five steps: sample preparation, image capturing, fiber detection and segmentation, shape analysis, and fiber classification. In sample preparation, a bundle of fibers is often embedded in a polymer resin, hardened and cut into slices of 1-4 m in thickness [11] [12]. The slices are then placed on a slide, and the embedding resin is removed by dissolving solvent.…”
Section: Introductionmentioning
confidence: 99%